Hubungan Komunikasi Terapeutik Perawat Dengan Tingkat Kecemasan Orangtua Yang Anaknya Di Rawat Di Ruang Amarylis Lantai 6 RSUD Khidmat Sehat Afiat: The Relationship Between Nurses' Therapeutic Communication and the Level of Anxiety of Parents Whose Children Are Being Treated in the Amarylis Room, 6th Floor, Khidmat Sehat Afiat Regional Hospital - Astuty, Ela Winda (Indonesian Scholar Journal of Nursing and Midwifery Science, 2025)
Introduction: Communication is a process of conveying information, meaning or understanding from the sender to the recipient. In everyday life, communication is an important means to establish relationships with others. Poor communication from nurses or lack of information from nurses often makes patients anxious especially their families. Anxiety response is the most common feeling experienced by parents when there is a health problem in their child. Parents feel that they have not received clear information about their child's health status. Methods: The research design used a cross-sectional method. The population in this study were all parents of patients whose children were treated in the Amarylis room on the 6th floor of the Khidmat Sehat Afiat Hospital. The data collection technique used purposive sampling with a sample size of 210 respondents. The analysis used was the chi-square test. Results: The p-value produced was 0,000 < 0,05. Based on the results of the statistical test with the chi-square test, the p-value produced was 0,000 < 0,05 which can be concluded that there is a relationship between nurse therapeutic communication and the level of anxiety of parents whose children are treated in the Amarylis room on the 6th Floor at Khidmat Sehat Afiat Hospital. Discussion: The relationship between therapeutic communication with nurses and the level of anxiety of parents whose children are treated in the Amarylis Room on the 6th floor at Khidmat Sehat Afiat Hospital.